Evaluation an aqueous extract of irradiated and non irradiated of Orthosiphon aristatus on zebrafish embryo (Danio rerio) through acute toxicity assay - Balan, Santhra Segaran; Manokaram, Punithaamalar; Maya, Sitell; Bahari, Hasnah; Mohd Uzid, Mahathir; Muhammad Danial, Muhammad Danial; Zainal Abidin, Azrina; Jesus, Arapoc Daryl; Rahmadi, Mahardian (Walailak University, 2022)
Background: Orthosiphon aristatus has been usually related to be powerful in curing many illnesses inclusive of post-partum remedy, anti-influence, rheumatism and stopping osteoporosis as a result of menopause. Objectives: Thus, this study was designed to differentiate the toxicity effect of non-irradiated and irradiated Orthosiphon aristatus at different dosage of 3, 6, 9 and 12 kilogray (kGy) on zebrafish embryo. Method: Survival rate, hatching rate, heart beat rate and scoliosis were observed and date were analysed using SPSS 25.00 windows. Result: The lethal dose (LC50) of non-irradiated Orthosiphon aristatus is 381.81 μg/mL compare to irradiated extract at 3 % is (371.27 μg/mL), 6 % (311.03 μg/mL), 9 % (160.72 μg/mL) and 12 % (140.18 μg/mL). Hatchability of zebrafish embryo for Orthosiphon aristatus extract decrease in the higher dosage of irradiated sample compared to non-irradiated sample. No presence of scoliosis was observed in all dosage of irradiated and non-irradiated of Orthosiphon aristatus. The heartbeat of zebrafish embryo treated with irradiated Orthosiphon aristatus specifically 12 % show decrease at 250 μg/mL concentration. Remaining dosage of irradiated and non-irradiated Orthosiphon aristatus show average heartbeat around 120-160 bpm. Conclusion: As conclusion, irradiated and non-irradiated of Orthosiphon aristatus is safe to be consumed due to its pharmaceutical effect but it still exhibited mild toxicity effect on zebrafish embryo.